REFLEXIVITY IN TEACHER EDUCATION: THE VALUE OF PSYCHOANALYTICALLY ORIENTED CLINICAL SUPPORT - Sandra CADIOU (Universitaria Publishing House, Craiova, 2021)
An original type of training for in-service teachers is proposed at the rectorate of Toulouse, France. On one hand, teacher training answers to a specific professional difficulty of the context, which has been expressed by a team of volunteer teachers. On the other hand, it is based on research and is conducted by a researcher and his.her theoretical framework, and a trainer. We present the example of a training course carried out in 2018-2019. Based on a psychoanalytically oriented clinical framework, it answered to the request of volunteer teachers facing difficulties with demotivation of their secondary school pupils. This co-constructed training was built on the principle of reflexivity and was based on the theoretical framework of clinical didactic (Terrisse & Carnus, 2009; Carnus & Terrisse, 2013) which studies teaching and learning phenomena under the hypothesis of the Freudian unconscious. Concepts from clinical didactic: the already-there, the report to the test, the deferred action... but also more broadly from psychoanalysis organise the training engineering based on three tools: personal writing, analysis of practice using video and individualised interviews. Through two clinical cases, those of Léda and Marc, we analyse the impact of the tools put in place, then we extend our discussion to the rest of the group in order to underline the interest of this approach